Reliable cooperative multicasting for MBS WiMAX traffic - Elrabiei, Sara Moftah; Habaebi, Mohamed Hadi (Elsevier, 2012)
Cooperative multicast communication techniques for emerging broadband multimedia 22 services over WiMAX reduces network resource consumption, by broadcasting the data 23 simultaneously to multiple users independently of their number, on a common shared 24 downlink channel. Users distributed around the cell face different channel conditions 25 due to fading, user location, mobility, and other related issues. Recently, several schemes 26 were reported in the literature that attempt to introduce cooperative multicasting reliably 27 and efficiently, some of which utilize subscribers with good-channel as Relay Agents (RAs) 28 to provide coverage for subscribers suffering bad-channel conditions but ignore the large 29 amount of energy consumed in the process. In this paper, we propose energy-efficient 30 cooperative multicasting schemes by properly selecting RAs based on their location, chan- 31 nel condition and coverage. By exploiting the channel state information (CSI) and the loca- 32 tion based service (LBS), three protocols based on nearest neighbor, transmission distance 33 and subscriber-subscriber interlink instantaneous CSI were proposed and implemented in 34 order to improve the system’s energy consumption performance. Number of RAs was var- 35 ied according to channel conditions on a frame-per-frame basis. This approach consider- 36 ably reduces the amount of energy consumed as proven by analysis and simulation 37 models, providing a lower cost coverage solution with no dereliction in achieved 38 throughput.